Developing New Strategies for the Treatment of Tuberculosis Employing Ruthnium(II)Quaterpyridyl Compexes - Pokhrel, Megh Raj; Gamage, Pubudu; Kalita, Mausam; Shi, Aibin; Bossmann, Stefan H. (Journal of Nepal Chemical Society, 2009)
A series of ruthenium(II)quaterpyridyl complexes has been synthesized as prototypes for mycobacterial channel blockers. These Ru(II)complexes show distinct changes in their luminescence spectra when bound to the porin MspA from M. smegmatis, which is a non-pathogenic relative of M. tuberculosis. By using HPLC, we have determined binding constants of the Ru(II)-complexes to MspA in phosphate buffer (0.05M, pH = 6.8) ranging from 5.2 x 109 M-1 (Ru-C2) to 1.8 x 109 M-1 (Ru-C4). Our findings indicate that channel blocking is a promising treatment strategy for mycobacterial infections. It appears to be also a viable approach towards luminescent nanostructures, because MspA features extraordinary stability.Keywords: Ru(II)complexe, porin MspA, mycobacterial infection, tuberculosisDOI: 10.3126/jncs.v23i0.2091Journal of  Nepal Chemical Society, Vol. 23, 2008/2009 Page:2-10.